Identity Based Consensus for Self-Governing Systems - Platt, Moritz (Cranfield University, 2020)
The selection of members is a challenge in decentralised record-keeping systems. In ‘permissioned’ systems, this crucial task is performed by a central authority or consortium. In ‘permissionless’ systems, however, the selection process is not trivial and comes with risks. Malicious actors, in a privileged position, can tamper with data, threatening the integrity of the system as a whole. Permissionless membership selection protocols, popularised with the dissemination of distributed ledger technology, have the objective of limiting the influence of a single entity on the wider network.They do so by approximating a participant’s legitimacy, to participate in record maintenance, through external or internal factors. These approximations come with downsides, in terms of attackability, system performance, supported use-cases and resource requirements. In this poster, I propose a prototypical membership selection protocol that uses the measure of personhood as an approximation of legitimacy. Interpreting a decentralised system as a political system, I frame the membership selection problem as one of political representation. I propose a protocol that democratically attributes a personhood score to members, thus creating a self-governing public decentralised system.This work in progress lays out a roadmap for the formal evaluation of self-governing public decentralised systems and describes the anticipated challenges in their implementation.
Keywords: 'DSDS20 Poster'; 'DSDS20'; 'Distributed Ledger Technology'; 'Self-Governance'; 'Consensus'; 'Information and Computing Sciences not elsewhere classified'; 'Computer System Security'